“Coral gardens” and their Denials. Culture, Environment and the Uncertainties of the Future - Mauro Van Aken (Antropologia)
“Coral Gardens and Their Magic” (1935) of B. Malinowski represents part of the “mythical legacy” of the foundation of cultural anthropology, it remains an unstudied book although it reveals an ancient and important denial and ambivalent tension in taking into account the relationships between cultures and environments. In these removed legacy, the dichotomy of culture/nature are posited and will later encounter new contradictions in reading the scenarios of environmental intensive changes, which are today at the heart in conceiving futures. This urges cultural anthropology to put back culture in the environment, as it happened at its foundation. Further, anthropology needs to reintegrate futures in its ethnographic tools not as scenarios of predictions but in the way cultures perceive, imagine and incorporate the future in their practices, in relation with non-human agents and within the wider critic of the hegemonic fascination for consumption that we have taken often for granted in our models of understanding.